BIAYA PERJALANAN FUZZY UNTUK PEMBEBANAN LALULINTAS - Nindyo Cahyo Kresnanto; Ofyar Z. Tamin (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2008)
Abstract The main factor in trip assignment models is the perception of trip makers about their travel costs. In real condition, trip makers usually do not obtain accurate information to estimate their travel costs. Travel costs are usually expressed using a linguistic term, such like “travel time from A to B is about 10 minutes”, which can not be measured precisely (values with a specific range). Using fuzzy method, the ”about” condition can be formulated in the term of fuzzy set with a value having lower-bound and upper-bound boundaries. The set is called fuzzy-travel-cost. In this paper, the trip assignment using fuzzy-travel-cost is compared with that using the deterministic travel cost. The result shows that fuzy-travel-cost model gives a better result than the deterministic travel cost model.Keywords: trip assignment model, fuzzy-travel-cost, fuzzy-shortest-path